¿Es posible (Re)insertar a los pobres al desarrollo?: Modelos y paradigmas - Ventura, José (2016)
Poverty is a difficult phenomenon to solve due to its complex and multidimensional character, which is why there are many definitions and ways of measuring it. In this context, this paper has as a main goal to present a review of literature of the diverse focuses and models of reduction of poverty and to proportionate a framework of analysis and reflection for future investigations. Methodologically, the paper of literature review, which is of descriptive and theoretical nature, pays especial interest in the proposals developed by Hernando De Soto (2000) and C.K. Prahalad (2005), who illustrate hope to face an endemic problem in an international level. The richness of each focus (its complementarity and integrality) defies the Management of Business because puts in evidence its potential contribution to the fight against poverty. The main result demonstrates that endogenous models, in which poor people are protagonists in the process of reinsertion to development, require two strategies: access to the markets and valorization of its wealth. Poor people require more from market (more capitalism) than from social programs subsidized by the Government.